Malocclusion after direct restorative treatment (Research, Society and Development, 2022)
Malocclusion is the abnormal alignment of teeth and the way in which the upper and lower teeth fit together. Normally, the upper teeth slightly overlap the lower ones. Among the means of treatment for malocclusion, there is restorative treatment, which can be classified as direct and indirect. For the purposes of this study, we chose to focus on direct restorative treatment. Therefore, this research aimed to analyze the best direct restorative treatment of malocclusion. It was sought to find among the direct restorers, the one that can be used in the treatment of malocclusions. In the methodology, an integrative literature review was carried out based on the periodic databases, PubMed, Google Scholar and Scielo, whose time frame was between the years 2017 to 2022. In the results, it was clear to see that the direct restorative treatment with the use of Composite resin proved to be the best alternative for the case presented, for presenting greater dental preservation, shorter clinical time, low cost, good surface smoothness, ease of polishing, among other advantages.